Morpho-anatomical characterisation, saponin content, and ITS-based DNA barcoding of Ngoc Linh ginseng (Panax vietnamensis Ha & Grushv.) cultivated under the forest canopy - Phúc, Đặng Ngọc; Hoàng, Tấn Quảng; Trần, Hữu Dũng; Nguyễn, Thanh Tùng (Hue University Journal of Science: Natural Science, 2026)
This study investigated the anatomical characteristics, saponin content, and DNA-ITS barcode markers to establish standardised criteria for identifying Ngoc Linh ginseng (Panax vietnamensis Ha & Grushv.) cultivated under the forest canopy in the Tra Linh Commune, Da Nang City. Morphological and anatomical traits were described. The rhizomes and roots were analysed for the total saponin content and major saponins – G-Rg1, M-R2, G-Rb1, and G-Rd. Genomic DNA was extracted from the leaves, and the internal transcribed spacer (ITS) region was sequenced. The results revealed that cultivated Ngoc Linh ginseng displayed typical species-specific morphological and anatomical features. The total saponin content was 13.81 ± 0.18%, with G-Rg1 at 3.647 ± 0.062%, M-R2 at 3.823 ± 0.054%, G-Rb1 at 0.979 ± 0.017%, and G-Rd at 0.961 ± 0.037%, conforming the requirements of the Vietnamese Pharmacopoeia V. ITS sequences from three samples were registered in GenBank (PV185794–PV185796) and showed 99.42–100% similarity with P. vietnamensis. These findings support a standardised protocol for identifying Ngoc Linh ginseng, enabling its conservation and sustainable development.